2018
DOI: 10.4236/ojpm.2018.84008
|View full text |Cite
|
Sign up to set email alerts
|

Fit “n” Cool Kids: Effects of Peer-Modeling and Goal Setting on Physical Activity

Abstract: Background: Decreasing the risk of overweight and obesity from an early age is imperative and efforts should focus on fostering children's physical activity (PA). Within school-based interventions, there is insufficient evidence on the effectiveness of the use of character peer-modeling and goal setting to increase physical activity. Therefore, the purpose of this study was to examine the impact of a school-based intervention on PA and enjoyment of PA in grades 3-5 elementary school age children at two urban e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Our findings are similar to other studies showing that goal setting using pedometers in elementary school aged children can have a positive effect on their physical activity levels (Burns, Brusseau, & Fu, 2017;Hardman, Horne, & Lowe, 2011;Horne, Hardman, Lowe, & Rowlands, 2009;Larson et al, 2018;Wilson, Sibthorp & Brusseau, 2017). This current study did not include rewards (Hardman et al, 2011;Horne et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are similar to other studies showing that goal setting using pedometers in elementary school aged children can have a positive effect on their physical activity levels (Burns, Brusseau, & Fu, 2017;Hardman, Horne, & Lowe, 2011;Horne, Hardman, Lowe, & Rowlands, 2009;Larson et al, 2018;Wilson, Sibthorp & Brusseau, 2017). This current study did not include rewards (Hardman et al, 2011;Horne et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The increases shown in this study couple with other study related to recess (Larson, Brusseau, Chase, Heinemann, & Hannon, 2014) and classroom physical activity breaks (Bershwinger & Brusseau, 2013) could have a significant impact on student health and behavior. Our findings are similar to other studies showing that goal setting using pedometers in elementary school aged children can have a positive effect on their physical activity levels (Burns, Brusseau, & Fu, 2017;Hardman, Horne, & Lowe, 2011;Horne, Hardman, Lowe, & Rowlands, 2009;Larson et al, 2018;Wilson, Sibthorp & Brusseau, 2017). This current study did not include rewards (Hardman et al, 2011;Horne et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown that adding 10% to step goals once a week is sufficient for increasing daily step counts. 39,40 Students who reached their goal were given a mean step increase of 10% at the end of each week; those students who struggled to meet their goal were given a mean step reduction of 10% to increase attainability and competence. Goals were provided individually from a personal note from the character models that the graduate students created each week and were distributed each Monday by the research assistants.…”
Section: Methodsmentioning
confidence: 99%
“…Goal setting has been identified as a leading psychological strategy for improving performance 37 and that goal setting can lead to behavior change due to the fact that they guide an individual’s attention and effort to obtain a specified level of proficiency. 38 More recently, studies have explored the role of characters with PA goals or targets both with 39 and without rewards 40 both showing successes in increasing PA.…”
mentioning
confidence: 99%